Improving rural doctors’ professional competence: effectiveness analysis of China’s village doctors policy - Li, Jiantao; Lian, Tinghui; Tian, Yayan; Wang, Yuxiao; Zhang, Jingru; Wu, Meichen (Frontiers in Public Health, 2025)
ObjectivesThis study aimed to analyze the impact of the Village Doctor Policy on the professionalization of village doctors.MethodsData were collected from a field survey conducted in Western China in 2023. The Professionalism Level Measurement Questionnaire was constructed using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) to ensure its validity. Propensity score matching (PSM) analysis was employed to compare the professionalization levels of village doctors in areas with and without policy implementation.ResultsThe sample had more males than females, with most participants aged 46–60 years (48.4%). Ordinary least squares (OLS) regression indicated that the policy positively influenced the professionalization of village doctors (p < 0.001), statistically significant effects on professional skills (β = 7.02, p < 0.01), professional conduct (β = 5.89, p < 0.05), and professional awareness (β = 6.34, p < 0.05). To address potential selection bias, PSM was conducted using three matching techniques. The average treatment effect on the treated (ATT) was 6.536 for k-nearest neighbor matching, 9.017 for caliper matching and 6.110 for kernel matching. These findings further confirmed the positive impact of the policy. The enhancement of professional skills, conduct, and awareness was found to be statistically significant (p < 0.05) under caliper matching.ConclusionThe Village Doctor Policy enhanced the professionalization of village doctors and strengthened Village doctor corps. This policy transformed the “half doctor, half farmer” status of village doctors to “unit members,” promoting their professional development and improving medical service quality. It is recommended that the government continue to promote localized rural employment policies to enhance the motivation and incentives of health care professionals.